2019
DOI: 10.1177/0165551519828627
|View full text |Cite
|
Sign up to set email alerts
|

Twitter sentiment analysis using fuzzy integral classifier fusion

Abstract: A thorough analysis of people’s sentiment about a business, an event or an individual is necessary for business development, event analysis and popularity assessment. Social networks are rich sources of obtaining user opinions about people, events and products. Sentiment analysis conducted using multiple user comments and messages on microblogs is an interesting field of data mining and natural language processing (NLP). Different techniques and algorithms have recently been developed for conducting sentiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…To obtain the classification result, a supervised k-nearest neighbor (KNN) classification algorithm [17] is used. KNN uses feature similarity where it assigns a data point based on how close it is to its neighbor.…”
Section: Data Classification Using Knnmentioning
confidence: 99%
“…To obtain the classification result, a supervised k-nearest neighbor (KNN) classification algorithm [17] is used. KNN uses feature similarity where it assigns a data point based on how close it is to its neighbor.…”
Section: Data Classification Using Knnmentioning
confidence: 99%
“…Different proposed classification and pure natural language processing (NLP)-based methods have different behaviours in predicting sentiment orientation [42]. The authors suggested that pure NLP-based methods have very low accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The focus of the literature, however, is based on sentiment analysis in political speeches in social media [28]. According to Emadi and Rahgozar [29], sentiment analysis has been extensively studied with the following five classification techniques: (a) classification using minimum Natural Language Processing (NLP) preprocessing as explained in Jurafsky and Martin [30], (b) pure NLP (lexicon semantic), (c) classification with rich NLP preprocessing and feature extraction, (d) graph-based clustering method and (e) method with classifier fusion approach. However, only the first three have been extensively used, while the latter have been neglected.…”
Section: Conceptual Framework In Social Mediamentioning
confidence: 99%
“…In this sense, our specific contribution in this work is twofold. First, we propose a framework that overcomes some of the limitations reported by Emadi and Rahgozar [29] who claimed that n-gram latent Dirichlet allocation (LDA) topic modelling, extraction and entity network and topic-based sentiment scores require a considerable amount of tagged data. Second, our approach allows a thorough analysis of retweets as a better approach to topic detection [31].…”
Section: Conceptual Framework In Social Mediamentioning
confidence: 99%